Nonlinear fiber loop mirror optimization to enhance the performance of multiwavelength brillouin/erbium-doped fiber laser - Al-Alimi, Abdulmoghni Ali Wazea; Yaacob, Mohd. Hanif; Abas, Ahmad Fauzi (Institute of Electrical and Electronics Engineers, 2014)
The performance of multiwavelength BEFL based on nonlinear fiber loop mirror (NOLM) optimization has been experimentally investigated. The NOLM is optimized to act as highly reflective mirror, which results in reducing the threshold power and enhancing the number of the generated Stokes lines at low EDF pump power as well. This design presents a low threshold power of 2 mW and generates up to 26 Stokes lines at EDF pump power of 25 mW.